Physical exercise as therapy for type 2 diabetes mellitus. Issue 1 (March 2014) - Balducci, Stefano; Sacchetti, Massimo; Haxhi, Jonida; Orlando, Giorgio; D'Errico, Valeria; Fallucca, Sara; Menini, Stefano; Pugliese, Giuseppe
Abstract Many studies have highlighted the importance of physical activity (PA) for health, and recent evidence now points to the positive improvements associated with exercise in type 2 diabetes mellitus (T2DM). However, few physicians are willing to prescribe exercise as a therapy for diabetic patients. In addition, there is a lack of information on how to implement exercise therapy especially in long‐term exercise regimens. The purpose of this manuscript is to summarize standards of exercise therapy for patients with T2DM, both in terms of prescribing and monitoring, according to the American College of Sports Medicine and the American Diabetes Association guidelines. We present details of the exercise therapies used in long‐term studies, describing how the parameters for exercise prescription were applied in clinical practice. These parameters are described in terms of frequency, intensity, duration, mode and rate of progression in long‐term therapeutic prescriptions. Individual responses to exercise dose are discussed, and critical issues to be considered in patients with underlying disease and in T2DM patients are highlighted. Copyright © 2013 John Wiley & Sons, Ltd.